Elbow Positioning and Joint Insufflation Substantially Influence Median and Radial Nerve Locations. Issue 11 (November 2015) - Hackl, Michael; Lappen, Sebastian; Burkhart, Klaus J.; Leschinger, Tim; Scaal, Martin; Müller, Lars P.; Wegmann, Kilian
Abstract: Background: The median and radial nerves are at risk of iatrogenic injury when performing arthroscopic arthrolysis with anterior capsulectomy. Although prior anatomic studies have identified the position of these nerves, little is known about how elbow positioning and joint insufflation might influence nerve locations. Questions/purposes: In a cadaver model, we sought to determine whether (1) the locations of the median and radial nerves change with variation of elbow positioning; and whether (2) flexion and joint insufflation increase the distance of the median and radial nerves to osseous landmarks after correcting for differences in size of the cadaveric specimens. Methods: The median and radial nerves were marked with a radiopaque thread in 11 fresh‐frozen elbow specimens. Three‐dimensional radiographic scans were performed in extension, in 90° flexion, and after joint insufflations in neutral rotation, pronation, and supination. Trochlear and capitellar widths were analyzed. The distances of the median nerve to the medial and anterior edge of the trochlea and to the coronoid were measured. The distances of the radial nerve to the lateral and anterior edge of the capitulum and to the anterior edge of the radial head were measured. We analyzed the mediolateral nerve locations as a percentage function of the trochlear and capitellar widths to control for differences regarding the size of the specimens. Results: The mean distance of the radial nerve to the lateral edge of the capitulum as a percentage function of the capitellar width increased from 68% ± 17% in extension to 91% ± 23% in flexion (mean difference = 23%; 95% confidence interval [CI], 5%‐41%; p = 0.01). With the numbers available, no such difference was observed regarding the location of the median nerve in relation to the medial border of the trochlea (mean difference = 5%; 95% CI, −13% to 22%; p = 0.309). Flexion and joint insufflation increased the distance of the nerves to osseous landmarks. The mean distance of the median nerve to the coronoid tip was 5.4 ± 1.3 mm in extension, 9.1 ± 2.3 mm in flexion (mean difference = 3.7 mm; 95% CI, 2.04‐5.36 mm; p < 0.001), and 12.6 ± 3.6 mm in flexion and insufflation (mean difference = 3.5 mm; 95% CI, 0.81‐6.19 mm; p = 0.008). The mean distance of the radial nerve to the anterior edge of the radial head increased from 4.7 ± 1.8 mm in extension to 7.7 ± 2.7 mm in flexion (mean difference = 3.0 mm; 95% CI, 0.96‐5.04 mm; p = 0.005) and to 11.9 ± 3.0 mm in flexion with additional joint insufflation (mean difference = 4.2 mm; 95% CI, 1.66‐6.74 mm; p = 0.002). Conclusions: The radial nerve shifts medially during flexion from the lateral to the medial border of the inner third of the capitulum. The median nerve is located at the medial quarter of the joint. The distance of the median and radial nerves to osseous landmarks doubles from extension to 90° flexion and triples after joint insufflation. Clinical Relevance: Elbow arthroscopy with anterior capsulectomy should be performed cautiously at the medial aspect of the joint to avoid median nerve lesions. Performing arthroscopic anterior capsulectomy in flexion at the lateral aspect of the joint and in slight extension at the medial edge of the capitulum could enhance safety of this procedure.